Knowledge and attitudinal factors influencing Malaysian individual investors’ annual report financial statements usage / Kishan Krishnen @ Ragavan - Kishan , Krishnen @ Ragavan (2018)
Financial statements are important sources of information about entities for stock investment decision-making. Yet, reliance on them is not universal among individual investors and it is unclear what affects their financial statements usage. The purpose of this thesis is to examine the influence of financial statement knowledge and attitudinal factors on Malaysian individual investors‘ annual report financial statement usage. Underpinned by human capital theory and the theory of planned behaviour, this quantitative study involves a survey of 399 individual investors in Malaysia. The research instrument is a self-administered questionnaire answered by individual investors who attended investment talks conducted by a major Malaysian stockbrokerage firm. Findings indicate that annual report financial statements usage is positively influenced by subjective norm, financial statement knowledge, financial statements usage attitude, perceived behavioural control and investment horizon attitude while negatively influenced by trading attitude and investing luck attitude. Diligence acts as a moderator on the relationship between financial statement knowledge and annual report financial statements usage. Statistically significant differences in financial statements usage were identified for gender, age group, education level, employment sector and investing experience, though not for ethnicity. It is hoped that findings of this study will be useful in the development of more effective investor education programmes that not only endow investors with greater financial knowledge but also shape attitudes that elicit positive long-term stock investing behavior.